Inter- and Intra-Species Diversity of Lactic Acid Bacteria in Apis mellifera ligustica Colonies - Iorizzo, Massimo (Microorganisms, 2020)
Lactic acid bacteria could positively affect the health of honey bees, including nutritional supplementation, immune system development and pathogen colonization resistance. Based on these considerations the present study evaluated predominant Lactic Acid Bacteria (LAB) species from beebread as well as from the social stomach and midgut of Apis mellifera ligustica honey bee foragers. In detail, for each compartment, the diversity in species and biotypes was ascertained through multiple culture-dependent approaches, consisting of Polymerase Chain Reaction-Denaturing Gradient Gel Electrophoresis (PCR-DGGE), 16S rRNA gene sequencing and Randomly Amplified Polymorphic DNA-Polymerase Chain Reaction (RAPD-PCR). The study of a lactic acid bacteria community, performed with PCR-DGGE and sequence analysis targeting the V1–V3 region of the 16S rRNA gene (rDNA), highlighted the presence of a few species, including Apilactobacillus kunkeei, Lactiplantibacillus plantarum, Fructobacillus fructosus, Levilactobacillus brevis and Lactobacillus delbrueckii subsp. lactis. Depending on the different compartments, diverse levels of biodiversity in species were found. Particularly, a very low inter-species biodiversity was detected in the midgut that was prevalently dominated by the presence of Apilactobacillus kunkeei. On the other hand, the beebread was characterized by a reasonable biodiversity showing the presence of five species and the predominance of Apilactobacillus kunkeei, Lactiplantibacillus plantarum and Fructobacillus fructosus. The RAPD-PCR analysis performed on the three predominant species allowed the differentiation into several biotypes for each species. Moreover, a relationship between biotypes and compartments has been detected and each biotype was able to express a specific biochemical profile. The biotypes that populated the social stomach and midgut were able to metabolize sugars considered toxic for bees while those isolated from beebread could contribute to release useful compounds with functional properties. Based on this knowledge, new biotechnological approaches could be developed to improve the health of honey bees and the quality of bee products.